Fragmented boundary zones between theory and practice in preschool teacher education in Sweden - Gustafsson Nyckel, Jan; Lander, Rolf; Thång, Per-Olof (Journal of Praxis in Higher Education, 2020)
Research dealing with preschool teacher education has been, for a long time, critical of a binary divide between theory and practice. Based on that issue, this study investigates a preschool teacher education programme in Sweden. It focusses on reflection upon theory and practice as an affordance offered to students in studies and work. The study used a questionnaire with two groups: campus students following the regular programme and students who were nurses already working at preschools. Analysis shows a fragmented education where the groups faced different problems, but also that neither of them could connect reflections on theory and practice at the workplace to their own learning approaches in either studies or working matters. How the students experienced affordances depended on their educational skills and knowledge, and the programme relied mostly on individual reflection as the solution to the binary divide. This reliance seemed to work better for campus students, who were challenged by the new environmental affordances. The students in the field-based programme were close to the preschools’ pedagogical micro-practice, which limited the possibility for critical reflection on theory and practice and its contextual conditions, especially for students who were nurses. Workplace routines seem to structure the students’ learning instead.